IMPACT OF HARMATTAN DUST ON ATMOSPHERIC ELECTRIC FIELD VARIABILITY IN NIGERIA’S MIDDLE BELT - Koffa, Jude Durojaiye; Olakunle, Ogunjobi (FUDMA JOURNAL OF SCIENCES, 2025)
The Harmattan season presents a unique natural laboratory for investigating aerosol-electricity interactions under extreme mineral dust loading conditions. We quantify the relationship between Saharan dust transport and atmospheric electric field enhancement using 30 months (Jan 2022–Jun 2024) of hourly electric field (field mill), PM2.5/PM10 (optical particle counter), and HYSPLIT back-trajectory measurements from Lokoja, Nigeria . Harmattan episodes demonstrate exceptional coupling between aerosol loading and electric field strength, following the power law relationship Fine-mode particles exhibit the strongest correlation with field enhancement while coarse particles show weaker associations . Source region analysis using HYSPLIT back-trajectories reveals systematic differences: dust events originating from the Bodélé Depression produce electric field peaks of , compared to , compared to for Western Saharan sources, reflecting variations in particle size distribution and mineralogical composition. Case studies of three major Harmattan events reveal characteristic temporal patterns with rapid onset and gradual recovery , indicating asymmetric dust mobilization and removal processes. Results indicate Lokoja observations robustly capture source-dependent dust-electricity coupling across the sampled transport corridors. This is the first multi-season, size-resolved demonstration that surface electric field can serve as a near-real-time proxy for fine dust transport and source attribution in the Sahel.